2016
DOI: 10.1007/s00253-016-7566-9
|View full text |Cite
|
Sign up to set email alerts
|

Formulations of polymeric biodegradable low-cost foam by melt extrusion to deliver plant growth-promoting bacteria in agricultural systems

Abstract: The extrusion technology of blends formed by compounds with different physicochemical properties often results in new materials that present properties distinctive from its original individual constituents. Here, we report the use of melt extrusion of blends made from low-cost materials to produce a biodegradable foam suitable for use as an inoculant carrier of plant growth-promoting bacteria (PGPB). Six formulations were prepared with variable proportions of the raw materials; the resulting physicochemical an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 57 publications
0
21
0
Order By: Relevance
“…Liquid inoculants simplify both the industrial production and the field application, although compared with solid formulations, such as peat- or polymer-based inoculants, bacteria in liquid inoculants appear to be more sensitive to stressful conditions and can exhibit decreased viability when used on seeds or soil (Herrmann and Lesueur, 2013 ). Effectiveness of PGPB inoculants has been improved by immobilization of inoculant cells in polymeric carriers, such as alginate and starch foam (Bashan et al, 2016 ; Marcelino et al, 2016 ). Thus, the actual demand is for improved liquid inoculant formulations, which are replacing peat-based inoculants and currently comprise ~80% of doses sold for soybean crops in Brazil (Hungria et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Liquid inoculants simplify both the industrial production and the field application, although compared with solid formulations, such as peat- or polymer-based inoculants, bacteria in liquid inoculants appear to be more sensitive to stressful conditions and can exhibit decreased viability when used on seeds or soil (Herrmann and Lesueur, 2013 ). Effectiveness of PGPB inoculants has been improved by immobilization of inoculant cells in polymeric carriers, such as alginate and starch foam (Bashan et al, 2016 ; Marcelino et al, 2016 ). Thus, the actual demand is for improved liquid inoculant formulations, which are replacing peat-based inoculants and currently comprise ~80% of doses sold for soybean crops in Brazil (Hungria et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have shown benefits in terms of the encapsulation of microbial inocula, increasing the survival time and establishment of microbes in the soil (Marcelino, Milani, Mali, Santos, & Oliveira, 2016). It is interesting that there were no significant differences in the total number of bacteria isolated from the soil that received the encapsulated microbial inoculum and the soil that received the nonencapsulated microbial inoculum (Figure 1).…”
Section: Resultsmentioning
confidence: 96%
“…Biological Sciences, v. 41, e43936, 2019 increased ammonium concentration in the soil that received alginate. Alginate is a polysaccharide and may serve as a carbon and energy source for heterotrophic soil bacteria, which need energy from plants (Marcelino et al, 2016). The alginate with or without inoculum did not increase the total number of bacteria in the soil (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, different concentrations of microorganisms in inoculant formulations (CFU mL -1 ) are reported: 10 9 (Reetha et al, 2014); 10 10 (Young et al, 2006); 10 6 (Marcelino, Milani, Mali, Santos, & Oliveira, 2016); 10 3 (O'Callaghan, 2016). Encapsulation demands high population density during inoculation in order to ensure the minimum population desired.…”
Section: Discussionmentioning
confidence: 99%